In vitro Evidence of Improved Antimicrobial Efficacy of Silver and Triclosan Containing Vascular Grafts Compared with Rifampicin Soaked Grafts. (March 2019) - Berard, Xavier; Puges, Mathilde; Pinaquy, Jean-Baptiste; Cazanave, Charles; Stecken, Laurent; Bordenave, Laurence; Pereyre, Sabine; M'Zali, Fatima
Abstract : Objectives: The aim was to compare the antimicrobial efficacy of four different grafts: a standard graft (Intergard, IG), an IG graft soaked in rifampicin (IGrif), a silver impregnated graft (Intergard Silver, IGS), and a silver + triclosan impregnated graft (Intergard Synergy, IGSy). Methods: This was a seven day in vitro study. The IG, IGrif, IGS, and IGSy grafts were each contaminated separately with the following microorganisms: Staphylococcus epidermidis, Methicillin resistant Staphylococcus aureus (MRSA), Escherichia coli, and Candida albicans from both clinical and American Type Culture Collection (ATCC) origins. The in vitro antimicrobial efficacy was evaluated by time to kill assays at T0, T24h, T48h, T72h, and T168h. Bactericidal activity was defined as >3 log10 reduction factor (logRF). Additionally, Rifampicin, triclosan and silver resistance development were screened. Results: As anticipated for the non-antimicrobial IG, all microorganism strains proliferated. The IGSy and the IGS showed a seven day bactericidal efficacy (>3 logRF) for all tested microorganisms. This efficacy was confirmed at all time points for IGSy only, demonstrating faster bactericidal efficacy than IGS. The IGrif demonstrated a seven day bactericidal efficacy against the ATCC MRSA only, while showing no activity against C. albicans and ATCC E. coli . Regarding ATCC S. epidermidis, clinical MRSA and clinical E. coli, IGrif, although bactericidal at earlier time points, lost its antimicrobial efficacy at seven days leading to the emergence of rifampicin resistant mutants in four of six, two of six, and two of six assays, respectively. Mutant strains were also detected in ATCC MRSA in one of six assays. No triclosan or silver resistance has emerged at T7days. Conclusion: For all microorganisms tested, the Synergy graft combining silver with triclosan demonstrated a more sustainable and efficient seven day antimicrobial activity than the rifampicin soaked graft. The emergence of rifampicin resistant mutants suggests preference for a Synergy graft over a graft soaked in rifampicin, to prevent or treat an infection when a biological solution is not feasible.